APPLICATION OF DATA MINING FOR CLASSIFICATION OF SALES BEST-SELLING PRODUCTS USING THE C5.0 ALGORITHM (Case Study of Syarah Bakery in the West Circle) - Perkoso, Bagus Hakim; Asnawati; Elfianty , Lena (Jurnal Komputer, 2023)
Data mining is the process of obtaining useful information from a large database and needs to be extracted so that it becomes new information and can assist in decision making. The purpose of this study is to apply data mining in classifying best-selling product sales using the C5.0 algorithmThe research method used is the Waterfall Method which is serial in nature which starts from the process of planning, analysis, design and implementation of the system. The C5.0 algorithm can handle continuous and discrete attributes. The first thing to do is to calculate the entropy value of all attributes, then calculate the highest information gain value of all attributes so that the attribute that will be used as the root or parent is obtained. The suggestion from the author is that the Data Mining Application can function later to find out which products are of interest and help plan future supply of stock.